RADIOGRAPHY OF OSSA PEDIS WITH SUSPECTIVE CORPUS ALIENUM AT DRS. H. AMRI TAMBUNAN REGIONAL HOSPITAL LUBUK PAKAM - Sri Nanda Sihotang; Juliana Lasniar Sidauruk (Yayasan Nuraini Ibrahim Mandiri, 2025)
Radiography of the ossa pedis (lower extremities) is an examination of the foot bones consisting of 26 bones and divided into 3 parts, namely, 7 ossa tarsalia, 5 ossa metatarsal, and 14 ossa phalanges using a general X-ray plane that aims to show or describe the structure of the bones in the pedis. Corpus alienum is the entry of foreign objects into the body abnormally, usually caused by gunshots, stabs, inhalation, swallowing in certain parts. The radiographic technique used is the dorso-plantar and lateral projections of the plane used is a fixed general radiography with a capacity of (500 mA) but the author only uses (200 mA) and image recording using Digital Radiography. The type of research used is qualitative and descriptive research by means of observation, interviews, data analysis then this research was conducted on April 10-May 10, 2025 in the radiology installation of Drs. H. Amri Tambunan Lubuk Pakam Hospital using a general X-ray unit.